1989
DOI: 10.1021/bi00438a015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the L.lambda. phase in trehalose-stabilized dry membranes by solid-state NMR and x-ray diffraction

Abstract: Solid-state nuclear magnetic resonance (NMR) spectroscopy and X-ray powder diffraction were used to investigate the mechanism of trehalose (TRE) stabilization of lipid bilayers. Calorimetric investigation of dry TRE-stabilized bilayers reveals a first-order phase transition (L kappa----L lambda) at temperatures similar to the L beta'----(P beta')----L alpha transition of hydrated lipid bilayers. X-ray diffraction studies show that dry mixtures of TRE and 1,2-dipalmitoyl-sn-phosphatidylcholine (DPPC) have a lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 32 publications
5
47
1
Order By: Relevance
“…2) indicate that at the highest temperature at which the lipid headgroups are rigid, the chains in the hydrated membrane are frozen (233 K) while the chains in the TRE-POPC membrane remain partly mobile (263 K). The deferred freezing of the acyl chains compared to the headgroup was also observed in TRE-DPPC membrane [6]. At the same temperature, the lipid chain dynamics is similar between the hydrated and the trehalose-protected POPC membranes, as seen, for example, in the 2 H spectra at 263 K (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…2) indicate that at the highest temperature at which the lipid headgroups are rigid, the chains in the hydrated membrane are frozen (233 K) while the chains in the TRE-POPC membrane remain partly mobile (263 K). The deferred freezing of the acyl chains compared to the headgroup was also observed in TRE-DPPC membrane [6]. At the same temperature, the lipid chain dynamics is similar between the hydrated and the trehalose-protected POPC membranes, as seen, for example, in the 2 H spectra at 263 K (Fig.…”
Section: Resultssupporting
confidence: 59%
“…We show here that trehalose-containing dry lipid membranes preserve the lipid bilayer structure while removing the headgroup and glycerol backbone motions at higher temperatures than the hydrated membranes, thus facilitating the measurement of protein-lipid distances. While the phase properties of trehalose-DPPC mixtures had been investigated by NMR before [6,7], a comparison of the conformation of the hydrated and trehalose-containing membranes for protein structure determination has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose preserves the lameller structure of dry membranes in the absence of water by replacing the hydration water around the lipid headgroups (48). Small amounts of trehalose raise the phase-transition temperature of the membrane compared with the hydrated bilayer, thus reducing lipid motion (49) and allowing the CODEX experiments to be conducted at milder temperatures (M.T., unpublished data). Experiments on hydrated and trehalose-containing POPC͞PG-1 membranes confirmed that the oligomeric state of PG-1 is the same between the two.…”
Section: Methodsmentioning
confidence: 99%
“…As known, sucrose does not undergo Millard reactions with the amino groups of proteins, as one of the non-reducing sugars it mainly accumulates as storage or regulatory solute in response to stress (Lee et al, 1989;Page-Sharp et al, 1999). The EPS layer surrounding cells creates a microenvironment that buffers the osmotic disequilibrium across the cell membrane preserving hypersaline conditions in marine algae (Liu and Buskey, 2000).…”
Section: Article In Pressmentioning
confidence: 99%